Remittance and Inflation - An Empirical Study for Vietnam - Hai, Nguyen Thi Hong; Doan, Thang (Asian Journal of Economic Modelling, 2017)
Remittances have recently received such a great attention as private monetary flows that its monetary nature seems to be disregarded. The issue that whether remittance flows are inflationary, resulting in a change in relative price, remains controversial. This study utilizes a reduced-form VAR model to investigate the inflation’s response to a positive shock to the remittance based on Ball et al. (2009)’s study. We use a quarterly data from 1st quarter 1996 to 3rd quarter 2012. The main findings are that first, there exists a positive effect of remittance on inflation in Vietnam and this effects prolong up to three quarters; second others main macroeconomic factors also affect inflation but at a lower magnitude compared with remittances.